Enhancing the Performance of PV Panel Undergoing Shading Effects - Monadhel Al-Chaderchi; K. Sopian; T. Salameh; D. Zhang; M. A. Alghoul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Experimental and simulation work were performed to study the effects of shading for different strings inside photovoltaic (PV) panels under real outdoor environmental climate conditions for Sharjah, United Arab Emirates. The electrical characteristics of PV panel were measured by using the PV analyzer, while the simulations were performed by MATLAB. The effect of full cell shading were studied experimentally for each configuration of two or four bypass diodes and verified by theoretical modeling. The I-V and P-V curves for all cases were recorded to investigate the effect of bypass diodes in reducing shading losses under similar environmental conditions. Compared to design with fewer bypass diodes, inserting more bypass diodes (four diodes in our work) contributed to higher yield in performance of solar PV panels undergoing shading while taking in to account the cost of energy production. Compared to the case of two bypass diodes, applying four diodes can recover up to ~31% of non-shaded maximum power under different cell shading conditions.